Anti-depressant medication use is a risk factor for incident knee surgery and opioid use in patients with knee osteoarthritis - Zheng, Yongqiang; Zhang, Jinshan; Wang, Zefeng; Liu, Xiaofeng; Xu, Yongquan; Fang, Yangzhen; Lin, Zhenyu; Lin, Liang (Frontiers in Psychiatry, 2023)
Objective To investigate whether depression and exposure to anti-depressant medication are independent risk factors for incident knee surgery and opioid use in knee osteoarthritis (KOA) patients. Methods We identified all patients who visited our outpatient department and were clinically diagnosed with KOA between January 2010 and January 2018. We retrieved their demographic, clinical, and radiographic data from the database of our hospital. Next, we analyzed the effect of depression and anti-depressant medication on the incident knee surgery and opioid use in KOA patients. Results A total of 4,341 KOA patients were found eligible to form the study population. Incident knee surgery and opioid use for the purpose of treating osteoarthritis were observed in 242 and 568 patients, respectively. Incident knee surgery was significantly associated with age (OR [95%CI], 1.024 [1.009–1.039], P = 0.002), BMI (OR [95%CI], 1.090 [1.054–1.128], P < 0.001), baseline K-L grade 3 (OR [95%CI], 1.977 [1.343–2.909], P = 0.001), baseline K-L grade 4 (OR [95%CI], 1.979 [1.241–3.157], P = 0.004), depression (OR [95%CI], 1.670 [1.088–2.563], P = 0.019), and exposure to anti-depressant medication (OR [95%CI], 2.004 [1.140–3.521], P = 0.016). Incident opioid use was significantly associated with depression (OR [95%CI], 1.554 [1.089–2.215], P = 0.015) and exposure to anti-depressant medication (OR [95%CI], 1.813 [1.110–2.960], P = 0.017). Conclusion Depression and anti-depressant drug exposure were independently associated with incident knee surgery, highlighting the need for more attention on comorbid depression in KOA management.